2009
DOI: 10.1007/s10551-009-0223-9
|View full text |Cite
|
Sign up to set email alerts
|

The Drivers of Green Brand Equity: Green Brand Image, Green Satisfaction, and Green Trust

Abstract: green brand image, green satisfaction, green trust, green brand equity, green marketing,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
1,103
0
107

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,070 publications
(1,255 citation statements)
references
References 54 publications
45
1,103
0
107
Order By: Relevance
“…This is also true for the green image which can improve consumer satisfaction and fulfil people's "green needs" (Chen, 2010). In practice, it can be shown that airlines do take active steps to improve their image through addressing environmental concerns.…”
Section: Image and Perceptionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is also true for the green image which can improve consumer satisfaction and fulfil people's "green needs" (Chen, 2010). In practice, it can be shown that airlines do take active steps to improve their image through addressing environmental concerns.…”
Section: Image and Perceptionmentioning
confidence: 97%
“…Given Chen's (2010) definition of green brand image, it is important for companies to show environmental commitment and concerns in order to generate a green image. In this respect, it is less important for these measures to be actually effective, but rather that they are perceived by the consumer to be effective.…”
Section: Perceived Effective Measures By Airlinesmentioning
confidence: 99%
“…First, the perceived importance of environment improvement by managers negatively affect to innovation performance. It is quite surprising because most of the previous literature pointed out that innovation improving environment leads to higher firm performance [37,[39][40][41][42][43]. Given that previous literature considered the output only, however, the result of this study does not counter the literature, but rather point to the possibility that the input that is required to perform environmental innovation is much higher than the actual output transformed from it.…”
Section: Resultsmentioning
confidence: 54%
“…Diverse studies found out the positive effect of green innovation on firm performance, such as material or energy reduction and environmental improvement [39][40][41][42][43][44]. In a similar vein, environmental marketing is found to affect positively to firms' capabilities [45,46].…”
Section: Sustainable Innovationmentioning
confidence: 97%
“…Especially for organic product of a customer trust can be assessed by four important cases which is the level of reliable, dependable, trustworthy, and expectations [18]. It is reviewed by researches on the previous organic vegetables products in Indonesia, that customer trust on organic vegetables product covers all four dimensions [3].…”
Section: Customer Trust On Organic Productsmentioning
confidence: 99%